Professional ASP.NET 2.0 Special Edition - Evjen, Bill; Hanselman, Scott; Rader, Devin; Muhammad, Farhan; Civakumār, Es (Wrox, 2006)
ASP.NET allows web sites to display unique pages for each visitor rather than show the same static HTML pages. The release of ASP.NET 2.0 is a revolutionary leap forward in the area of web application development. It brings with it a wealth of new and exciting built-in functions that reduce the amount of code you'll need to write for even the most common applications. With more than 50 new server controls, the number of classes inside ASP.NET 2.0 has more than doubled, and in many cases, the changes in this new version are dramatic. This book will alert you to every new feature and capability that ASP.NET 2.0 provides so that you'll be prepared to put these new technologies into action. Greatly expanded from the original best-selling Professional ASP.NET 2.0, this new special edition adds hundreds of pages of new coverage of advanced and new techniques relating to data and data sources, the provider model, personalization, membership, role management, localization, configuration, migration, and Altas. Bonus CD-ROM and DVD The bonus DVD includes a 180-day trial of Microsoft Visual Studio 2005 Professional The accompanying CD-ROM features a valuable library of chapters from other key Wrox books. It contains more than 1,000 pages from more than 15 Wrox ASP.NET 2.0, C# 2005, VB 2005, .NET 2.0, and SQL Server 2005 books. What you will learn from this book The idea of the server control and its pivotal role in ASP.NET development How to create templated ASP.NET pages using the new master page feature Techniques for debugging and handling errors How to work with data from enterprise databases including SQL Server 2005 and Oracle(r) Ways to package and deploy ASP.NET applications How to retrieve, update, and delete data quickly and logically How to implement the cultures and regions features to localize your web site into multiple languages for different visitors How to use the new "Altas" add-in for ASP.NET 2.0 to add Ajax-style capabilities to your ASP.NET applications An understanding of how to use and extend the new pro?vider model for accessing data stores, processes, and more How to keep track of your application's performance and health with new monitoring tools When and how to migrate your ASP.NET 1.x applications to 2.0 Who this book is for This book is for experienced programmers and developers who are looking to make the transition to ASP.NET 2.0. Wrox Professional guides are planned and written by working programmers to meet the real-world ...